From armed roots to airline routes in South America: A dual imprinting perspective - Qiao, Kunyuan; Hiatt, Shon R.; Sine, Wesley D. (Strategic Management Journal, 2026)
Abstract Reserch Summary We propose that founding partner relationships can leave distinct imprints on organizations that differ in durability and in how they respond to subsequent changes involving the founding partner. Examining South American airlines founded between 1919 and 1984, we argue and find that such relationships simultaneously create an internal capability imprint, enhancing operational performance and facilitating international expansion, and an external identity imprint, constraining expansion by triggering national security concerns among foreign regulators. Internal capabilities persist longer because they are embedded in organizational structures and tacit knowledge, while external identity resides in more malleable stakeholder perceptions. Post‐founding changes to the imprinter reshape these effects asymmetrically: the transition to civilian air traffic control erodes the competitive advantage of military‐derived capabilities by diffusing previously scarce expertise, while military coups intensify the negative consequences of a military‐associated identity. These findings advance a dual imprinting perspective and contribute to strategy research by explaining persistent organizational heterogeneity through founding‐era capabilities and identities. Managerial Summary When launching a venture, founders instinctively seek to collaborate with powerful partners such as celebrated investors and high‐profile board members. Those relationships leave two distinct legacies. The first is operational: the knowledge and systems a powerful partner brings embed themselves deeply, sharpening capabilities that sustain competitive advantage for years. The second is reputational: the outside world immediately begins to categorize your organization through that association, and that categorization can be hard to escape. Our research on South American airlines shows how military‐era founding partners produced operational excellence that fueled international growth, while simultaneously creating a security‐sensitive identity that blocked market access in politically sensitive contexts. The lesson for founders: think several moves ahead. The question is not solely what this partner can give us today, but how will we be seen if his or her reputation shifts tomorrow.